Pengaruh Suhu Vacuum Drying Terhadap Sifat Fisiko Kimia Antosianin Ubi Jalar Ungu (Ipomoea batatas var. Ayamurasaki) Yang Dienkapsulasi Dengan Maltodekstrin - Arnoldus Alvin Adra Manao (BiSTeK Pertanian, 2021)
. Indonesia's natural resource potential makes it a fertile country with a wide variety of flora and fauna. One of the most widely produced food crop commodities in Indonesia is sweet potato. Sweet potato (Ipomoea batatas L.) is an important food source and has the potential to be used as feed and industrial raw materials. Extraction is a separation process based on differences in material solubility. The extraction process has the main parts, namely the solvent and the main ingredient. Extraction of anthocyanins from purple sweet potato tissue was carried out by maceration with 96% ethanol. The results of the extraction are then encapsulated using maltodextrin. After that it is dried in a vacuum dryer.